2017
DOI: 10.4103/ijo.ijo_752_17
|View full text |Cite
|
Sign up to set email alerts
|

Uveal effusion syndrome in 104 eyes: Response to corticosteroids – The 2017 Axel C. Hansen lecture

Abstract: Purpose:The purpose of the study was to investigate the corticosteroids for uveal effusion syndrome (UES).Methods:Retrospective series of 104 eyes with UES treated with oral corticosteroids (OCS), periocular corticosteroids (PCS), topical corticosteroids (TCS), or observation (OBS). Main outcome measure was UES resolution.Results:Of 104 eyes, treatment included OCS (n = 27), PCS (n = 12), TCS (n = 11), and OBS (n = 54). A comparison of the four groups (OCS vs. PCS vs. TCS vs. OBS) revealed differences in those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
3
29
1
2
Order By: Relevance
“…UES may be difficult to diagnose as it may mimic many entities. Shields in his study on 104 eyes reported a mean age of 70 years [ 10 ]. However, the study specifically evaluated Type 3 UES with normal sclera using ultrasound or MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UES may be difficult to diagnose as it may mimic many entities. Shields in his study on 104 eyes reported a mean age of 70 years [ 10 ]. However, the study specifically evaluated Type 3 UES with normal sclera using ultrasound or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used treatment is surgery involving the creation of surgical sclerostomies (scleral window surgery) or partial thickness sclerectomies to support transscleral drainage [ 1 , 8 , 9 ]. In some cases, steroids or NSAID may be effective [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some ophthalmologists tried medical treatment for uveal effusion syndrome with oral steroid. Shield et al treated 104 eyes of uveal effusion syndrome with corticosteroids 17 Bausili et al used CO2 laser 18 and control was achieved in 95% cases in reports but according to others, surgical treatment was only effective option for treatment of idiopathic uveal effusion syndrome. We have found that surgical sclerectomies using partial thickness resection was very effective.…”
Section: Discussionmentioning
confidence: 99%
“…In 1963, Schepens and Brockhurst first reported uveal effusion syndrome (UES) in which they described the pathology as choroidal detachment, often with secondary retinal detachment, optic disc swelling, and minimal signs of uveitis [13].…”
Section: Discussionmentioning
confidence: 99%